2020
DOI: 10.1016/j.jacr.2020.01.030
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria® Crohn Disease

Abstract: Three common clinical scenarios involving use of imaging in Crohn disease are covered. These include the initial evaluation of Crohn disease when the diagnosis has not been previously established, the evaluation for anticipated exacerbation of known disease, and the evaluation of disease activity during therapy monitoring. The appropriateness of a given imaging modality for each scenario is rated as one of three categories (usually appropriate, may be appropriate, usually not appropriate) to help guide evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 119 publications
0
14
0
Order By: Relevance
“…Cross-sectional imaging methods are increasingly gaining ground, becoming essential in the diagnosis and follow-up of patients with Crohn's disease, although their utility is limited in the initial stages of the disease, when the lesions are still subtle and limited to the mucosa. Currently, CTE is the cross-sectional method of choice in the evaluation of such patients at most health care facilities and is the method recommended by the American College of Radiology in most clinical situations related to Crohn's disease (39) , although MRE has also shown very high accuracy. In addition, recent studies have demonstrated that MRE has become the reference standard in the assessment of the inflammatory activity of the disease, especially in perianal manifestations (40) .…”
Section: Resultsmentioning
confidence: 99%
“…Cross-sectional imaging methods are increasingly gaining ground, becoming essential in the diagnosis and follow-up of patients with Crohn's disease, although their utility is limited in the initial stages of the disease, when the lesions are still subtle and limited to the mucosa. Currently, CTE is the cross-sectional method of choice in the evaluation of such patients at most health care facilities and is the method recommended by the American College of Radiology in most clinical situations related to Crohn's disease (39) , although MRE has also shown very high accuracy. In addition, recent studies have demonstrated that MRE has become the reference standard in the assessment of the inflammatory activity of the disease, especially in perianal manifestations (40) .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 367 consecutive patients with CD with no history of bowel surgery and who had undergone MRE between July 2019 and February 2020 at Asan Medical Center, a tertiary referral center, were initially recruited. The indications for MRE in CD at our institution were consistent with those recommended [2,11] for the baseline or followup assessment for medical therapy. After reviewing the technical notes taken at the time of MRE examination, to avoid confounding effects on bowel distention, we excluded three patients who did not receive the complete oral fluid administration required for MRE, leaving a study cohort comprising 364 patients (269 male and 95 female; mean age ± standard deviation, 31.2 ± 9.4 years).…”
Section: Study Participantsmentioning
confidence: 69%
“…Magnetic resonance enterography (MRE) and computed tomography enterography (CTE) are the primary imaging modalities used to evaluate patients with Crohn's disease (CD) [1][2][3]. Owing to the absence of radiation exposure, Flattening in the Anteroposterior Direction of the Terminal Ileum or Sigmoid Colon Lying Across the Psoas Muscle on Magnetic Resonance Enterography in Patients with Crohn's Disease MRE is particularly useful for patients with CD, who tend to be young and require lifelong repetitive examinations [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It provides high resolution, multiplanar reformatted images [13][14][15]. CTE is the fastest and the most appropriate imaging modality for evaluating active inflammatory bowel disease and its complications [16]. The only disadvantage of this technique is the radiation exposure [17].…”
Section: Discussionmentioning
confidence: 99%